Prognostic Nutritional Index (PNI) at Admission Predicts In-Hospital Mortality of COVID-19-Infected Patients - Haryati, Haryati; Isa, Mohamad; Rudiansyah, Mohammad; Juhairina, Juhairina; Nor, Muhamad; Arganita, Fidya Rahmadhany (Majalah Kedokteran Bandung, 2025)
Corona Virus Disease-2019 (COVID-19) was declared a pandemic in March 2020 and caused considerable deaths in all parts of the world. Mortality is influenced by the immune system status and increased vulnerability to infection, both related to nutritional status. The Prognostic Nutritional Index (PNI), calculated using lymphocyte count and albumin levels, may have the ability to more accurately characterize the nutritional and inflammatory conditions of COVID-19 patients. This retrospective study analyzed 967 COVID-19 patients at Ulin Hospital Banjarmasin, Indonesia, by examining demographic data, laboratory results, and PNI in relation to survival outcomes. The study revealed that factors such as age, sex, comorbidities (including hypertension, diabetes mellitus/DM, obesity, etc.), number of comorbidities, and disease severity correlated with mortality. Leucocyte count, lymphocyte count, albumin levels, and PNI all showed significant correlations with survival (p<0.001), suggesting that these factors may serve as useful prognostic indicators for COVID-19 patient’s survival. The PNI was associated with an increased risk of mortality, with a univariate odds ratio (OR) of 0.923. Receiver operating characteristic (ROC) analysis demonstrated that a PNI cut-off value of p<41.9 had a sensitivity of 44.9% and a specificity of 82.4%, with an area under the curve (AUC) of 0.666 (p<0.001). Hence, PNI at admission, which reflects patients' immune system and nutritional status upon hospital admission, can be used as a simple, cost-effective, and reliable predictor of mortality in COVID-19 patients.